The IUCN Global Standard for Nature-based Solutions™ as a tool for enhancing the sustainable development of marine aquaculture - Le Gouvello, Raphaëla; Cohen-Shacham, Emmanuelle; Herr, Dorothee; Spadone, Aurélie; Simard, François; Brugere, Cécile (Frontiers in Marine Science, 2023)
This paper applies the IUCN Global Standard for Nature based Solutions™ self-assessment tool (published in 2020) to two aquaculture case studies. Data from the case studies were compiled by the authors. In Zanzibar, secondary data were obtained through a previous project, which included a stakeholder workshop in Zanzibar (in 2019) and one deliverable published by the IUCN on Zanzibar of their catalogue “Aquaculture and Marine Conservation”. In Indonesia, the original data were provided by the Blue Natural Capital Funding Facility (BNCFF) and the associated local teams. The analysis of the data, the information provided, and the scoring itself were done by the authors, in association with local teams in both areas. The results of the two assessments, discussed in the paper and presented in detail in the Supplementary materials, can be considered original research, never previously published in a scientific journal. The concept of Nature-based Solutions (NbS) was proposed by the International Union for Conservation of Nature (IUCN) to protect, restore, and sustainably manage natural and modified ecosystems for achieving a variety of societal benefits. The IUCN released the IUCN Global Standard for NbS™ to help design, assess, strengthen, and upscale NbS interventions. In the current context of growing uncertainties for the future of coastlines and oceans, aquaculture has been recognized as a positive activity for achieving sustainable development in coastal communities; supporting food security, poverty alleviation, and economic resilience; and contributing to the conservation of marine ecosystems in some cases. However, the sustainability of aquaculture systems has often been criticized. Aquaculture initiatives in coastal areas can achieve both nature conservation and sustainable development objectives, but reflection on the conditions under which this would happen is needed. This article examines aquaculture systems through the lens of the NbS concept and the IUCN Global Standard for NbS™, along with other sustainability concepts and instruments currently used in the context of aquaculture. The application of the IUCN Global Standard for NbS™’s to two case studies is explored: seaweed farming in Zanzibar in marine conservation areas and shrimp farming coupled with mangrove restoration in Indonesia. The results show that the NbS concept underpinning the IUCN Global Standard for NbS™ could help in the overall assessment of aquaculture systems and improve their sustainability by highlighting both their positive outcomes and issues requiring further examination in relation to marine biodiversity benefits, socio-economic development, and/or governance. The IUCN Global Standard for NbS™ could provide an operational framework to implement existing concepts, such as the Ecosystem Approach to Aquaculture, contribute to clarifying critical issues in aquaculture development, and provide guidance for the development of a new type of aquaculture project, specifically designed as NbS. This finding advocates the context-dependent exploration and promotion of aquaculture projects as NbS.